Application of The DMAIC Method in Improving The Quality of Electric Power Steering Housing Products - Azwir, Hery Hamdi; Fanani, Zaenal; Oemar, Hirawati (Universitas Ahmad Dahlan, 2022)
PT. ABC is a manufacturing company that produces Electric Power Steering (EPS) Housing components. For the past three months, there have been problems with the EPS production process. The problem is related to the finding of defective products which on average reached 3.9% of the total production, and has exceeded the maximum limit allowed by the company, which is 2%. This study aims to overcome these problems by making improvements using the DMAIC method in the hope of finding the root cause of the emergence of defects and making improvements to reduce the number of defects that occur. The improvement results have shown that the number of defects reduced from 3086 pcs to 1948 pcs per 22 working days or decreased by 0.54% with an increase in sigma level from 3.95 to 4.01 sigma. In this case, DMAIC implementation is effectively reduced defects by 1.5% based on the sigma level. To achieve a 6-sigma level equivalent to a world-class industry, companies must make continuous improvements by fixing other root causes.